Leveraging Gamification for Learning & Development Programs to Drive Employee Engagement: Case of Indian IT Employees - Shreya Sharma (International Journal of Advanced Science and Technology, 2020)
Gamification utilizes gaming features and game dynamics in a non-game set up. The main objective of gamification is enhancing the learner’s engagement and experience. It is thus utilised in LMS (Learning Management Systems) and e-Learning Systems. Research has shown that there is a direct relationship between increased employee engagement and motivation with introduction of gamification intervention in learning and development. The current research paper studied the case of Indian IT employees by conducting a study on 119 participants (Indian IT employees) to understand how gamification can be leveraged in learning and development programs to drive employee engagement, with respect to Information Technology companies. This research work contributes to the study of utilization of gamification in learning and development. The researcher concluded with theoretical and practical implications of the impact of gamification on employee engagement.